2017
DOI: 10.1016/j.dcn.2017.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Event-related potential response to auditory social stimuli, parent-reported social communicative deficits and autism risk in school-aged children with congenital visual impairment

Abstract: Communication with visual signals, like facial expression, is important in early social development, but the question if these signals are necessary for typical social development remains to be addressed. The potential impact on social development of being born with no or very low levels of vision is therefore of high theoretical and clinical interest. The current study investigated event-related potential responses to basic social stimuli in a rare group of school-aged children with congenital visual disorder… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
11
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 79 publications
3
11
2
Order By: Relevance
“…Ratings of strengths and difficulties (SDQ) further indicated that peer relationships are an area of concern for children with VI. Difficulties in social function have been consistently observed across pre-school, middle childhood, and adolescents in congenital VI (Bathelt et al, 2017;Greenaway et al, 2017;Jure et al, 2016;Tadić et al, 2010). Reported difficulties were most pronounced for children with S/PVI, but ratings in the MVI group overlapped with both the S/PVI and control group.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ratings of strengths and difficulties (SDQ) further indicated that peer relationships are an area of concern for children with VI. Difficulties in social function have been consistently observed across pre-school, middle childhood, and adolescents in congenital VI (Bathelt et al, 2017;Greenaway et al, 2017;Jure et al, 2016;Tadić et al, 2010). Reported difficulties were most pronounced for children with S/PVI, but ratings in the MVI group overlapped with both the S/PVI and control group.…”
Section: Discussionmentioning
confidence: 99%
“…Difficulties in the social domain may arise due to multiple influences. First, social cognition may develop differently in children with VI (Bathelt et al, 2017;Dale & Salt, 2008), potentially because salient social information like facial expressions are less accessible to children with congenital VI. Other constraints may arise from reduced opportunities for social interaction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In early sensory processing, a greater N100 response to the subject’s own name (SON) versus an unfamiliar name has been reported for both adults [5,6] and school-aged children [7], although this may reflect detection of a familiar name rather than SON specifically [6]. Multiple studies have identified another early ERP response, believed to be an index of pre-attentive auditory detection, called SON negativity [810].…”
Section: Introductionmentioning
confidence: 99%
“…Key and colleagues demonstrated that children 4–12 years of age exhibited increased P300 responses to both SON and the name of a familiar other in a passive oddball paradigm [19]. Finally, Bathelt et al examined ERP response to SON and an unfamiliar name in eight- to twelve-year-old typically developing children and children with congenital visual disorders [7]. Results indicated an enhanced N100 response to SON in both groups and a SON negativity component in the typically developing children that was attenuated over mid-central and right-frontal regions in the visually impaired group.…”
Section: Introductionmentioning
confidence: 99%